HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN DRIBLING SEPAK BOLA PADA EKSTRAKURIKULER SISWA MA AL KHAIRIYAH RANGSANG - Tahrer, Tahrer; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT This study aims to determine agility determine whether there is a relationship with the football dribbling ability Extracurricular ALKhairiyah Rangsang MA students, in this study a sample of the entire population of students who take extracurricular student of SMAN 1 Kandis with a total of 18 people. From the results of calculations can be seen that large correlation value agility with the ability dribling football in extracurricular MA students ALKhairiyah Rangsang is 0597 or 0597 count equal to the value r In the table values (Product Moment) (5%) of = 0468, or 0597> 0468 this means r calculate> r table, meaning that Ho is rejected means that the hypothesis is accepted linear regression models. After the correlation number obtained, further testing the hypothesis by using t-test Significance formula. From the results of the calculation are known t = 2974 while ttabel with dk = n-2 = 18-2 = 16 at 95% confidence level is 1.746. Ho hypothesis testing criteria accepted if thitung smaller than ttable, but the results of the calculations show that (t count> t table) or 2,974> 1,746., And is therefore null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that "there is a relationship agility with the ability dribling football in extracurricular MA students ALKhairiyah stimuli. "accepted.Keywords : Agility, Dribbling